Expression pattern and role of Foxcl during hair follicle morphogenesis - Manda, Juziel K (Department of Human Biology, 2024)
he murine Foxcl, which encodes a forkhead/winged helix transcription factor, 1s expressed in many embryonic tissues including prechondrogenic and peri-ocular mesenchyme, meninges, endothelial cells and kidney. Homozygous Foxe] null mice embryos die at birth with hydrocephalus, eye defects, and multiple skeletal abnormalities identical to those of the classical mutant, congenital hydrocephalus. Although the structure and function of murine Foxe] has been analyzed in many embryonic tissues, relatively little is known about the expression and role of this gene in the skin. To determine the Foxe] expression pattern during embryonic and neonatal skin development, this study utilised mice in which the Lac-z reporter gene was placed under the control of wild-type Foxcl promoter by homologous combination (Kume et al, 1998, Cell 93, 985-996). Lac-z encodes enzymatically active ~-galactosidase, which converts the colourless chromogenic 5-bromo-4-chloro-3-indolyl-~, Dgalactoside (X-gal) into a blue product enabling visualization of the Foxe] expression pattern. Skin samples from heterozygous and homozygous mutant mouse embryos (13.5-18.5 dpc) and neonates (P0-P7) were fixed in 4% PFA, stained for ~- galactosidase activity and processed for histology. Foxe] expression was detected by the presence of the blue colour. The results show that Foxe] is specifically expressed in the epithelial cells of the hair follicles at all stages of embryonic skin development. In the developing hair follicles Foxcl promoter activity is induced at high levels in the post-mitotic precursor cells of the hair shaft, inner root sheath and sebaceous gland of the pelage hair and whisker follicles. In mature anagen hair follicles, high levels of Foxcl are persistently detected in the keratogenous zone of the hair and sebaceous gland. Within the sebaceous glands, Foxcl was strongly expressed in cells that are located at the centre of the gland. Within the Foxcl-expressing compartments, most cells do not exhibit the nuclear proliferation marker BrdU. Co-localisation of Foxe] and apoptotic marker TUNEL was detected in keratogenous zone of the hair and in cells located closer to the sebaceous gland duct. Foxe] expression switched off during telogen. These results XVI suggest that Foxe] expression is associated with the transition from a proliferative to a post-mitotic state and that Foxe] may be involved in initiation of terminal differentiation and keratinization. High levels of Foxe] are maintained in fully differentiated hair keratinocytes and sebocytes possibly as one of the earliest events that perhaps trigger programmed cell death (apoptosis). The second objective of this study was to investigate the development of hair follicles in a mutant in order to determine the role of Foxcl. Hair follicle development was analysed in skin samples of homozygous mutant mouse embryos (13.5-l 8.5 dpc) using histological, immunocytochemical and histomorphometrical methods. Different stages of hair follicle morphogenesis were defined on the basis of accepted morphological criteria (Paus et al., 1999, J. Invest. Dermatol.; 113(4): 523-32.) Histological examination showed that hair follicle development was induced normally on the back of Foxcl mutant embryos at around 13.5 (dpc), with epidermal cells forming a hair plug (stages 1 and 2). Between 14.5 dpc - 15.5 dpc, the skin formed a completely penetrant bulbar hair follicle phenotype, which had initiated development of the inner root sheath characteristic of stages 4-5 of follicular development. Similarly, histological examination of Foxe] null follicles from 15.5 dpc to around birth showed no gross morphological defects in the hair shaft compartment where Foxe] is expressed. Quantitatively, embryonic skin showed no significant differences in rate of growth and number of hair follicles between Foxe] null mutants and wild types (P>0.05). These morphological findings suggest that the initial signalling events in embryonic hair development are independent of Foxe]. In conclusion, histological examination of the mutant skin shows that pelage hair follicle formation is initiated and proceeds normally up to the formation the bulbar hair follicles (stages 5) with no recognisable effects on the total number of induced hair follicles. The results show that Foxcl signalling is not required for induction and early development of hair follicle in embryos. Foxcl signalling, however, is likely to be essential for regulating differentiation of post-natal hair and sebaceous gland. Fmiher studies to determine how Foxe] signalling regulates post-natal hair follicle differentiation will be an excellent area for future research.